O orçamento público participativo como instrumento de efetivação da cidadania (avaliando a experiência de Fortaleza) - Gadelha, Ana Lúcia Lima (2010)
A participatory democracy is achieving a central position in government. Among these experiments, the Participatory Budget - PB, which has been gaining attention, including internationally, presents itself as a successful experience of comanagement, more democratic relationships between government and society. Its object is to discuss the budget of the city in which people act on the major issues and priorities, allowing for dialogue and discussion in the spaces created by the PB. Studies agree that the PB allows its participants to exercise an active citizenship, contributing to the development of spaces for popular participation. This research aimed to study the management tool called democratic participatory budgeting implemented by the management of the Municipal City hall of Fortaleza in the period 2005-2008, working with the hypothesis that this mechanism for public participation contributes to the practice of active citizenship of their participants. What we perceive in this research is that participation actually contributes to civic education of householders, as the results showed different perceptions and views on the process, and the exercise of social control. The research made use of qualitative and quantitative methodology, using among other instruments, semi-structured interviews and questionnaires of the survey type. This study enables us to state that the experience of PB in Fortaleza, although a very recent experience with a short analysis period, is bringing favorable conditions for the exercise of active citizenship.